2017
DOI: 10.1002/adfm.201606352
|View full text |Cite
|
Sign up to set email alerts
|

Mesh‐on‐Mesh Graphitic‐C3N4@Graphene for Highly Efficient Hydrogen Evolution

Abstract: Mesoporous materials have attracted considerable interest due to their huge surface areas and numerous active sites that can be effectively exploited in catalysis. Here, 2D mesoporous graphitic‐C3N4 nanolayers are rationally assembled on 2D mesoporous graphene sheets (g‐CN@G MMs) by in situ selective growth. Benefiting from an abundance of exposed edges and rich defects, fast electron transport, and a multipathway of charge and mass transport from a continuous interconnected mesh network, the mesh‐on‐mesh g‐CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(92 citation statements)
references
References 38 publications
4
88
0
Order By: Relevance
“…In general, the intensity of the D and G peaks represents the quantities of disordered and graphitized carbons; in addition, the intensity ratio of the sp 3 carbon to sp 2 carbon ( I D / I G ) can be used to evaluate the amount of disordered carbon or structural defects . The I D / I G ratio of Co 2 P@N,P‐C/C increased to 1.16, which indicated that more structural defects and disordered carbon were created by doping with N and P heteroatoms . Furthermore, the I D / I G ratio of Co 2 P@N,P‐C/CG was 1.03, which indicated a better graphitization degree after the introduction of the RGO.…”
Section: Resultsmentioning
confidence: 97%
“…In general, the intensity of the D and G peaks represents the quantities of disordered and graphitized carbons; in addition, the intensity ratio of the sp 3 carbon to sp 2 carbon ( I D / I G ) can be used to evaluate the amount of disordered carbon or structural defects . The I D / I G ratio of Co 2 P@N,P‐C/C increased to 1.16, which indicated that more structural defects and disordered carbon were created by doping with N and P heteroatoms . Furthermore, the I D / I G ratio of Co 2 P@N,P‐C/CG was 1.03, which indicated a better graphitization degree after the introduction of the RGO.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure b, the D and G bands of Ni 2 P@N, P−C/GN‐0.4 were found at 1355 and 1585 cm −1 . The stronger intensity ratio of Ni 2 P@N, P−C/GN‐0.4 ( I D / I G =1.08) than GO ( I D / I G =0.97) indicated the reduction from GO to GN, accompanying the increased structure defects and disorders in the composite . The nitrogen absorption and desorption curves of Ni 2 P@N, P−C/GN‐0.4 in Figure c were the type IV isotherm with a typical hysteresis loop, indicating the abundant mesopores in the sample.…”
Section: Resultsmentioning
confidence: 97%
“…Figure a shows the high‐resolution C 1s XPS spectra of GCN, GCNP, and GCNP 0.50 . The spectrum of GCNP 0.50 shows a C 1s peak at 285.5 eV, which represents sp 2 ‐hybridized carbon atoms bonded to nitrogen in aromatic form, and 289.1 eV, which represents tertiary carbon atoms attached to NH 2 [C–(N) 3 ] as compared with pure GNP (283.8 eV: sp 2 C–C; 286.7 eV; C–O, O–C=O) and GCN [284.5 eV: sp 2 C–C; 288.1 eV: C–(N) 3 ] . Figure b shows the N 1s spectra of photocatalysts GCN and GCNP 0.50 .…”
Section: Resultsmentioning
confidence: 99%
“…g‐C 3 N 4 and graphene, owing to their conductive and catalytic behaviors, would appear be good candidates for a composite . There are only a few reports in the literature relating to graphene/g‐C 3 N 4 composites . However, to the best of our knowledge, there is no report on the vacuum preparation of g‐C 3 N 4 /graphene nanoplatelet composites (GCNPs) for use in the photodegradation of tetracycline hydrochloride.…”
Section: Introductionmentioning
confidence: 99%